THE INFLUENCE-FACTOR OF CYCLING AS PHYSICAL ACTIVITY IN ELDERLY POST COVID-19 - Cahyo Setiawan; Suci Muqodimatul Jannah (Poltekkes Kemenkes Semarang, 2022)
As the age increases, the number of deaths caused by Covid-19 becomes prominent. In China, 3,6% of people aged 60-69 years died, followed by 8% of those aged 70-79 years because older people commonly experienced various comorbidities such as cardiovascular, diabetes, chronic respiratory disease, and hypertension. Therefore, if older people perform cycling consistently as an exercise, it would increase their immunity and derive long-term benefits. This study was a descriptive-quantitative study aimed to describe the factors that influence physical activity, specifically cycling, in aged-people post-Covid-19. The International Physical Activity Questionnaire (IPAQ) has been used to collect the information. The results showed that 88,6% of elderly people cycle because they know about the importance of exercise in health. In terms of age, the people aged between 55 and 60 years old were dominated by cycling with 29% of them being female.